Effects of Curcuma Zedoaria (Shoti) on Growth Performance and Hemato-Biochemical Parameters in Broiler (Research in Agriculture Livestock and Fisheries, 2020)
The experiment was conducted on “Cobb-500” broiler chicks to study the effects of Curcumazedoaria (shoti) on growth performances and haemato-biochemical parameters. A total of twentybroilers chicks (16 days old) were randomly divided into five equal groups (n=4). Three groups ofbroilers fed shoti powder at the rate of 10%; 20%; 30% (w/w) with other ingredients for 22 days.Broilers chicks fed on maize-soybean were considered as positive control while non-protein controlwas regarded as negative control. The results showed that body weight of broilers fed 10% and 20%shoti meal grew very close to those of control (maize-soybean) group. After having completed thefeeding trial, the birds were sacrificed to collect blood sample for and biochemical analysis .Weightsof different organs and length of intestine were also measured. Results showed that decreaseddressed weight, weight of skin and liver were found in 30% shoti treated group compared to proteincontrol group. Intestinal weight was highest in 30% shoti treated group but length was similar to theprotein control group. Total erythrocytes count, hemoglobin content and PCV value were founddecreased in shoti treated group compared to protein control group but ESR value was highest in10% shoti treated group. Total cholesterol was found to be decreased in the birds fed on shoticompared to protein control and significantly higher than non-protein control group. Triglyceride valuedecreased in 10% shoti treated group compared to protein and non-protein control group. IncreasedHDL value was found in 10% shoti treated group compared to control groups and 20 % and 30 %shoti treated groups. Result of this experiment showed that body weight of birds significantly (p